2019
DOI: 10.1167/iovs.18-25922
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gene Polymorphisms With Primary Open Angle Glaucoma: A Systematic Review and Meta-Analysis

Abstract: for genetic studies of POAG. All case control studies investigating the association between singlenucleotide polymorphisms (SNPs) and POAG risk were included. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated by fixed-or random-effect model. RESULTS. This meta-analysis included 108 case control studies involving 35,389 POAG patients and 51,742 controls. The pooled results showed a significant association between 20 SNPs in 12 genes (148Asp/Glu in APE1 gene; rs449647 in APOE gene; rs1052990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 145 publications
1
36
0
3
Order By: Relevance
“…61 We speculate that the strength of association noted between APOE ε4 and POAG will depend on the proportion of NTG patients enrolled in a given study, which may explain some of the variability in the published individual studies [33][34][35][36][37][38][39][40][41][42] and meta-analyses. [43][44][45][46][47] What is the mechanism by which APOE ε4 may be protective in glaucoma? APOE is expressed in a variety of cell types in the healthy retina and the optic nerve, including Müller glia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 We speculate that the strength of association noted between APOE ε4 and POAG will depend on the proportion of NTG patients enrolled in a given study, which may explain some of the variability in the published individual studies [33][34][35][36][37][38][39][40][41][42] and meta-analyses. [43][44][45][46][47] What is the mechanism by which APOE ε4 may be protective in glaucoma? APOE is expressed in a variety of cell types in the healthy retina and the optic nerve, including Müller glia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42] Several meta-analyses found no association between APOE and glaucoma, 43,44 while others reported an association between the APOE ε4/ε4 genotype and POAG in Asians. 45,46 Another large meta-analysis reported an association between a single-nucleotide polymorphism (SNP) in the promoter region of APOE (rs449647) and glaucoma 47 ; this SNP, however, is not associated with AD. 48 Interestingly, APOE ε4 is associated with decreased risk for another common neurodegenerative disease of the eye, age-related macular degeneration (AMD), [49][50][51][52] opposite of its effect on AD.…”
mentioning
confidence: 99%
“…Several studies have revealed a significant role of the myocilin, optineurin, and cytochrome CYP1B1 genes in glaucoma development [13][14][15][16]. Moreover, genome-wide association studies have shown associations of sequence variants [17][18][19][20][21] and single-nucleotide polymorphisms [22][23][24][25][26] with POAG. Notwithstanding the role of genetic mutations and variations on glaucoma onset, the role of different systemic risk factors remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset contains the raw data (supplementary Table), frequencies of alleles and genotypes ( Table 1 ) for three SNPs of two MMP genes (rs1799750 MMP1 , rs3918242 and rs17576 MMP9 ) in Russian patients diagnosed with POAG, EH, and PU. These polymorphisms were previously reported for their association with POAG, EH, and PU ( Table 2 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . The studied SNPs manifest the regulatory potential ( Table 3 ), which is evidenced by several eQTLs ( Table 4 ) and splicing QTLs ( Table 5 ).…”
Section: Data Descriptionmentioning
confidence: 57%